Odpowiedzi

2010-04-08T18:39:29+02:00
V=s/t ;s
s = V x t

P=mF ;F
mF = P /: m
F = P/m

E=mgh ;h
mgh = E /: mg
h = E/mg

K=a/R ;R
a/R = K
a/K = R
R = a/K

y=0,25x ;x
0,25x = y /: 0,25
x = y/0.25
x = y : 25/100
x = y x 100/25
x = y x 4
x = 4y

k=1/4n ;n
1/4n = k /: 1/4
n = k : 1/4
n = 4k

y=2t-1 ;t
2t - 1 = y
2t = y + 1 /: 2
t = (y + 1) : 2
2 4 2
2010-04-08T18:46:47+02:00
V=s/t*t y=0,25x/:0,25
v*t=s/t*t y/0,25=0,25x/0,25
v*t=s y/0,25=x

P=mF/:m
P/m=mF/m y=2t-1/:2-1
P/m=F y/2-1=2t-1/2-1
y/2-1=t
E=mgh/:mg
E/mg=mgh/mg
E/mg=h

K=a/R/*R
K*R=a/R*R
K*R=a
a=K*R/:K
a/K=K*R/K
a/K=R
Może pomogłam :)